Comparative Study on the Analgesic Effect of Fresh Moringa Oleifera Juice with Ibuprofen in Albino Mice - S Bhuvaneshwari, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Comparative Study on the Analgesic Effect of Fresh Moringa Oleifera Juice with Ibuprofen in Albino Mice